2021
DOI: 10.3748/wjg.v27.i8.708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of berberine on hyperglycaemia and gut microbiota composition in type 2 diabetic Goto-Kakizaki rats

Abstract: BACKGROUND A recent investigation showed that the prevalence of type 2 diabetes mellitus (T2DM) is 12.8% among individuals of Han ethnicity. Gut microbiota has been reported to play a central role in T2DM. Goto-Kakizaki (GK) rats show differences in gut microbiota compared to non-diabetic rats. Previous studies have indicated that berberine could be successfully used to manage T2DM. We sought to understand its hypoglycaemic effect and role in the regulation of the gut microbiota. AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 52 publications
4
31
0
1
Order By: Relevance
“…Notably, a recent study in diabetic Goto-Kakizaki rats showed that BBR improved metabolic parameters (including weight, FBG, GLP-1, and homeostatic model assessment-IR); however, the investigators observed significantly lower Bacteroidetes levels and B/F ratio, as well as decreased Muribaculaceae and increased Allobaculum levels. Further analysis showed a correlation between certain microbial communities and metabolic parameters (Zhao et al, 2021). As mentioned earlier, there is a crosstalk between the antidiabetic and antiobesity effects of BBR.…”
Section: Antidiabetic Effects Of Berberine By Regulating Gut Microbiotasupporting
confidence: 57%
“…Notably, a recent study in diabetic Goto-Kakizaki rats showed that BBR improved metabolic parameters (including weight, FBG, GLP-1, and homeostatic model assessment-IR); however, the investigators observed significantly lower Bacteroidetes levels and B/F ratio, as well as decreased Muribaculaceae and increased Allobaculum levels. Further analysis showed a correlation between certain microbial communities and metabolic parameters (Zhao et al, 2021). As mentioned earlier, there is a crosstalk between the antidiabetic and antiobesity effects of BBR.…”
Section: Antidiabetic Effects Of Berberine By Regulating Gut Microbiotasupporting
confidence: 57%
“…However, low bioavailability and an unidentified pharmacological mechanism are the main barriers to clinical application of berberine [ 27 ]. In addition to its pharmacological anti-diabetic roles in peripheral organs, it has been shown that berberine inhibits the function of disaccharide, promotes the release of GLP-1 to regulate metabolism, and modulates the component part of intestinal microbiota [ 28 ]. However, whether berberine could ameliorate intestinal glucose absorption received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…When these factors are abnormal, they can cause lipid metabolic disorders and pathophysiological changes in the related organs, hyperlipoproteinemia, lipidosis, and the resulting clinical syndromes, such as obesity, ketoacidosis, fatty liver, and neonatal scleredema ( 20 ). Statins are commonly used drugs for the treatment of dyslipidemia, but such drugs may bring many adverse effects, such as liver and kidney dysfunction, abnormal neuromuscular responses, increased risk of diabetes, and cognitive decline ( 21 ). Accumulating evidence suggests that gut flora structure is closely related to the development of lipid metabolism disorders ( 22 ).…”
Section: Discussionmentioning
confidence: 99%